Thermo-Catalytic Treatment of Used Lubricant by Using Cobalt Oxalate as Catalyst (1% by Wt.) (International Journal of Scientific Research in Science and Technology, 2024)
Increase in vehicles and machineries resulting in increased lubricant consumption and after prolonged use it is replaced by fresh one, generating huge volume of used lubricant. In addition to hydrocarbon, used lubricants also contain heavy metallic particles, combustion products and the organic compounds and other contaminants. Some of the contaminants present in used lubricants are extremely difficult to remove and may harm the environment if not disposed of properly. In this study Cobalt oxalate is used as a catalyst for thermos-catalytic process and cracking reaction is carried out by using 1.0% (by wt.) cobalt oxalate under optimized reaction conditions. The effect of temperature, flow rate, and catalyst concentration on conversion of used lubricant into valuable lighter hydrocarbon products were systematically evaluated. The catalyst used can be recycled and regenerated by catalytic regeneration processes and can be reused. Hence, by the catalyst recycling and regeneration the thermo-catalytic treatment can be more beneficial, as results demonstrate the potential of cobalt oxalate as an effective catalyst for conversion of used lubricant oil into valuable lighter products, contributes to the development of sustainable and environment friendly waste management strategy. The results obtained from the experiment studied on a cracked product are described.